Is a Mass Prevention and Control Program for Pandemic (H1N1) 2009 Good Value for Money? Evidence from the Chinese Experience - Biyan Wang; Jinliang Xie; Pengqian Fang (Tehran University of Medical Sciences, 2012)
Background: In order to provide guidance on the efficient allocation of health resources when handling public health emergencies in the future, the study evaluated the H1N1 influenza prevention and control program in Hubei Province of China using cost-benefit analysis.Methods: The costs measured the resources consumed and other expenses incurred in the prevention and control of H1N1. The assumed benefits include resource consumption and economic losses which could be avoided by the measures for the prevention and control of H1N1. The benefit was evaluated by counterfactual thinking, which estimates the resource consumption and economic losses could be happened without any measures for the prevention and control, which have been avoided after measures were taken to prevent and control H1N1 in Hubei Province, these constitutes the benefit of this project.Results: The total costs of this program were 38.81 million U.S. dollars, while the total benefit was assessed as 203.71 million U.S. dollars. The net benefit was 164.9 million U.S. dollars with a cost-effectiveness ratio of 1:5.25.Conclusions: The joint prevention and control strategy introduced by Hubei for H1N1 influenza is cost-effective.